Pengembangan Jaringan Kerja, Kolaborasi Antar-UMKM Desa Pematang Serai: Peran SDM Dalam Meningkatkan Sinergi dan Pertumbuhan Bersama - Arifin, Daud; Suwarno; Wahyono, Teguh (JUBDIMAS ( Jurnal Pengabdian Masyarakat), 2023)
The activity "Network Development, Collaboration Between MSMEs in Pematang Serai Village: The Role of Human Resources in Increasing Synergy and Shared Growth" is an initiative that aims to strengthen the relationship between micro, small and medium enterprises (MSMEs) units in Pematang Serai Village. This research explores how network development and collaboration between MSMEs can contribute to synergy and shared growth at the local level. Through a participatory approach, various business actors in Pematang Serai Village engage in training activities, workshops, and discussion sessions to increase their understanding of the benefits of collaboration. In an ever-changing global context, these efforts are directed at building the sustainability and resilience of local economies by optimizing the potential of human resources (HR). The result of this activity is an increase in awareness and collaboration capabilities among MSMEs, encouraging the exchange of knowledge and resources, and stimulating sustainable business growth. Through strong partnerships between MSMEs, it is hoped that Pematang Serai Village can better face future challenges and opportunities, and have a positive impact on the local economy and the community as a whole.